Targeting ApoC3 Paradoxically Aggravates Atherosclerosis in Hamsters With Severe Refractory Hypercholesterolemia - Xu, Yitong; Guo, Jiabao; Zhang, Ling; Miao, Guolin; Lai, Pingping; Zhang, Wenxi; Liu, Lili; Hou, Xinlin; Wang, Yuhui; Huang, Wei; Liu, George; Gao, Mingming; et al. (Frontiers in Cardiovascular Medicine, 2022)
Rationale: ApoC3 plays a central role in hydrolysis process of triglyceride-rich lipoproteins mediated by lipoprotein lipase (LPL), which levels are positively associated with the incidence of cardiovascular disease (CVD). Although targeting ApoC3 by antisense oligonucleotide (ASO), Volanesorsen, markedly reduces plasma triglyceride level and increases high density lipoprotein cholesterol (HDL-C) in patients with hypertriglyceridemia (HTG), the cholesterol-lowering effect of ApoC3 inhibition and then the consequential outcome of atherosclerotic-cardiovascular disease (ASCVD) have not been reported in patients of familial hypercholesterolemia (FH) with severe refractory hypercholesterolemia yet. Objective: To investigate the precise effects of depleting ApoC3 on refractory hypercholesterolemia and atherosclerosis, we crossed ApoC3-deficient hamsters with a background of LDLR deficiency to generate a double knockout hamster model (LDLR-/-XApoC3-/-, DKO). Approach and Results: On standard laboratory diet, DKO hamsters had reduced levels of plasma triglyceride and total cholesterol relative to LDLR-/- hamsters. However, upon high cholesterol/high fat (HCHF) diet feeding for 12 weeks, ApoC3 deficiency reduced triglyceride level only in female animals without affecting refractory cholesterol in circulation, whereas apolipoprotein A1 (ApoA1) levels were significantly increased in DKO hamsters with both genders. Unexpectedly, loss of ApoC3 paradoxically accelerated diet-induced atherosclerotic development in female and male LDLR-/- hamsters, but ameliorated fatty liver in female animals. Further analysis of blood biological parameters revealed that lacking ApoC3 resulted in abnormal platelet indices, which could potentially contribute to atherosclerosis in LDLR-/- hamsters. Conclusions: In the present study, our novel findings provide a new insight into the application of ApoC3 inhibition for severe refractory hypercholesterolemia and ASCVD.